TINDAK KEKERASAN TERHADAP ANAK DI SEKOLAH: Bentuk dan Aktor Pelaku - wahyu pramono; Dwiyanti Hanandini (Jurnal Administrasi Publik dan Pemerintahan, 2022)
The iceberg phenomenon has become a popular expression of the widespread non-violence against children that is spreading in Indonesia. This phenomenon shows that the social symptoms of acts of violence against children appear small on the surface but in reality are bigger than what is visible on the surface. The scene of acts of violence against children no longer only occurs in the private sphere but has entered the public sphere. Schools are one of the places where violence against children is often the center of attention. Actors who commit acts of violence against children can be carried out by teachers against students or between students. This study aims to examine the forms and actors of violence in schools. Acts of violence that occur in schools are still relatively few and only limited to acts of physical and psychological violence. Both forms of violence are not high in intensity. Bullying is a form of violence that is mostly done by female students, while acts of physical violence in the form of fights and threats are mostly done by male students. Meanwhile, teachers or other stakeholders were not found to have committed acts of violence. There are four times that are considered to be prone to acts of violence against children, namely during recess, after school, changing class hours and empty classes. Most of the incidents of violence occurred in the environment outside the school rather than in the school environment. Although outside the school environment, the place is not far from the school, just outside the school fence. Behind the school and outside the school near the river are the most vulnerable places used by school students to commit acts of violence. These places are often used by male students to gather there.